2019
DOI: 10.1177/0049475519834804
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A infection related haemophagocytic syndrome: a case report and systematic review

Abstract: Haemophagocytic lymphohistiocytosis (HLH) is a clinical syndrome of excessive inflammation and tissue destruction owing to abnormal immune activation. We report an unusual case of haemophagocytosis associated with hepatitis A virus (HAV) infection in a 21-year-old man. This was further complicated by haemolysis secondary to G-6-PD deficiency and fungal sepsis. Our patient was treated successfully with intravenous immunoglobulin (IVIg) and supportive care. A systematic review of all reported cases of HAV associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Moreover, HLH can result from infection with hepatitis viruses, with the majority of cases involving HAV and, less commonly, HBV or HCV infection [92][93][94]. Two systematic reviews of HAV-associated HLH cases have identified hepatomegaly and splenomegaly as distinguishing features of HAV-HLH, as these signs are rarely observed in patients with HAV infection who do not develop HLH [63,95]. Also, they noted that thrombocytopenia could be an early sign of HAV-HLH [63,95].…”
Section: Hepatitis Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, HLH can result from infection with hepatitis viruses, with the majority of cases involving HAV and, less commonly, HBV or HCV infection [92][93][94]. Two systematic reviews of HAV-associated HLH cases have identified hepatomegaly and splenomegaly as distinguishing features of HAV-HLH, as these signs are rarely observed in patients with HAV infection who do not develop HLH [63,95]. Also, they noted that thrombocytopenia could be an early sign of HAV-HLH [63,95].…”
Section: Hepatitis Virusesmentioning
confidence: 99%
“…Two systematic reviews of HAV-associated HLH cases have identified hepatomegaly and splenomegaly as distinguishing features of HAV-HLH, as these signs are rarely observed in patients with HAV infection who do not develop HLH [63,95]. Also, they noted that thrombocytopenia could be an early sign of HAV-HLH [63,95]. However, while hyperferritinemia can occur solely due to HAV infection, higher levels may indicate the presence of HLH [63].…”
Section: Hepatitis Virusesmentioning
confidence: 99%
See 1 more Smart Citation